Designing and Developing Digital Computer Game of Plastic Waste Awareness for Young Children - Frans, Octavianus; Zufri, Tubagus; Hilman, Dodi (Bina Nusantara University, 2024)
Providing education about how to behave or make decisions using game media will enable children to develop positive attitudes in dealing with waste problems which increasingly require our thoughts together. The design method through the stages of observation in the form of visual data search, analysis elaboration mapping problem, then visually determining the essential character as the main idea. The result is a character design with the function that allows player to know the existence of the threads. The game is made to arouse the interest of the players about anticipating plastic waste. This game is made in a 2-dimensional form which conveys information regarding the condition of the plastic waste which is described as attacking and filling the sea. Thus, actions will appear that will foster a sense of care for environmental cleanliness. The prototype of digital computer game was developed using scratch. The result of this prototype will be used for next development.